Minimally invasive basilic vein transposition in the arm or forearm for autogenous haemodialysis access: A less morbid alternative to the conventional technique - Ankush Jairath (Taylor & Francis Group, 2017)
Objective: To devise a minimally invasive, less morbid yet effective alternative technique for basilic vein transposition (BVT) in the arm/forearm and to compare perioperative outcomes with the conventional technique. Patients and methods: Patients undergoing BVT in the last two years (June 2013 to June 2015) were included in the study and the results were analysed. All patients were preoperatively evaluated using colour Doppler ultrasonography performed by the operating surgeon himself. For minimally invasive BVT, two or three small 1–2 cm incisions were made to completely mobilise the basilic vein, transposed in an anterolateral arm/forearm tunnel, and then anastomosed to the brachial or radial artery in the forearm and arm, respectively. The incision in the conventional technique was along the full length of the basilic vein, with the rest of the procedure remaining the same. Complications, pain, analgesic use, maturation and primary patency rates were compared between the techniques. Results: In all, 30 patients underwent minimally invasive BVT and 34 patients underwent conventional BVT, with mean age of 52 and 55 years, respectively. The complications of wound haematoma (one vs four) and wound infection/dehiscence (two vs six) were less common in the minimally invasive BVT group compared to the conventional group. The analgesic requirement and visual analogue scale pain score was significantly less in the minimally invasive BVT group. All other variables assessed, such as maturation and primary patency rate at 1 year, were not significantly different between the groups. Conclusion: Minimally invasive dissection of the basilic vein for vascular access transposition is a safe, reliable procedure with patency and functional outcomes comparable with those of conventional BVT.